2017
DOI: 10.14311/app.2017.13.0109
|View full text |Cite
|
Sign up to set email alerts
|

Variationally-Based Effective Dynamic Thickness for Laminated Glass Beams

Abstract: Abstract. Laminated glass, consisting of glass layers connected with transparent foils, has found its applications in civil, automotive, or marine engineering. Due to a high contrast in layer properties, mechanical response of laminated glass structures cannot be predicted using classical laminate theories. On the other hand, engineering applications demand easy-to-use formulas of acceptable accuracy. This contribution addresses such simplified models for free vibrations of laminated glass beams, with the goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…On the other side, it is experimentally proved that high vibration frequencies for EVA films -like for viscoelastic interlayers in general -typically have a stiffening effect, and this can be positively quantified in a possible moderate increase in shear bond efficiency(Knight et al 2022, Hána et al 2019). However, it is also experimentally observed that repeated mechanical loads (even at high strain rate) induce a marked reduction in the material stiffness, with deterioration of shear bond rigidity(Schmidt et al 2017). In such a variable and uncertain scenario, both the metal frame at the edges (Fig.3 (c)) and the fixing brackets (Fig.3 (d)) -that can be efficiently characterized by numerical analysisfurther contribute to modify the vibration response of the PV system, compared to ideal simplified restraints.5 / 12 Article 10.47982/cgc.9.614 Challenging Glass Conference Proceedings -Volume 9 -June 2024…”
mentioning
confidence: 99%
“…On the other side, it is experimentally proved that high vibration frequencies for EVA films -like for viscoelastic interlayers in general -typically have a stiffening effect, and this can be positively quantified in a possible moderate increase in shear bond efficiency(Knight et al 2022, Hána et al 2019). However, it is also experimentally observed that repeated mechanical loads (even at high strain rate) induce a marked reduction in the material stiffness, with deterioration of shear bond rigidity(Schmidt et al 2017). In such a variable and uncertain scenario, both the metal frame at the edges (Fig.3 (c)) and the fixing brackets (Fig.3 (d)) -that can be efficiently characterized by numerical analysisfurther contribute to modify the vibration response of the PV system, compared to ideal simplified restraints.5 / 12 Article 10.47982/cgc.9.614 Challenging Glass Conference Proceedings -Volume 9 -June 2024…”
mentioning
confidence: 99%